Oxaliplatin-induced acute ST segment elevation mimicking myocardial infarction: a case report - Weidner, Kathrin; Behnes, Michael; Haas, Jenny; Rusnak, Jonas; Fürner, Paul; Kruska, Mathieu; Mukherji, Agnibh; Borggrefe, Martin; Hofheinz, Ralf-Dieter; Akın, Ibrahim (Oncology research and treatment, 2018)
BACKGROUND: Oxaliplatin is a platinum-based antineoplastic agent used for the treatment of colorectal cancer and other gastrointestinal tumors. In combination with 5-fluorouracil for instance it is given in the so-called FOLFOX regimen in patients with colorectal cancer in the adjuvant as well as the palliative treatment setting. Cumulative neuropathy is a common cause of treatment discontinuation. Other toxicities are generally tolerable and managed by dose reductions and/or supportive treatment. While chronic cardiotoxic effects of cytostatics are well described, there are few reports on acute cardiotoxic reactions. - CASE REPORT: The present case describes the sudden development of a transient coronary vasospasm in a 56-year-old male patient mimicking an acute ST segment elevation myocardial infarction during systemic treatment with oxaliplatin. - CONCLUSION: Oxaliplatin is one of the most commonly used cytostatics for gastrointestinal cancer. Coronary vasospasm has never been reported for oxaliplatin. Thus it is crucial to keep in mind that acute cardiotoxic side effects may occur, even with chemotherapeutic agents without a prior evidence-based description of such events.